Non-inflammatory Physiology of “Inflammatory” Mediators – Unalamation, a New Paradigm - Maddipati, Krishna Rao (Frontiers in Immunology, 2020)
Many small molecules (mostly lipids derived from polyunsaturated fatty acids) and proteins (e.g. cytokines and chemokines) are labeled as inflammatory mediators for their role in eliciting physiological responses to injury. While acute inflammatory events are controlled by anti-inflammatory drugs, lasting damage to the tissues as a result of persistent inflammation is increasingly viewed as the root cause of many chronic diseases that include cardiovascular, neurological, and metabolic disorders, rheumatoid arthritis, and cancer. Interestingly, some of the ‘inflammatory’ mediators also participate in normal developmental physiology without eliciting inflammation. Anti-inflammatory drugs that target the biosynthesis of these mediators are too indiscriminate to distinguish their two divergent physiological roles. A more precise definition of these two physiological processes partaken by the ‘inflammatory’ mediators is warranted to identify their differences. The new paradigm is named ‘unalamation’ (ˈənˈəlAmāSH(ə)n) to distinguish from inflammation and to identify appropriate intervention strategies to mitigate inflammation associated pathophysiology without affecting the normal developmental physiology.